Anonymus Italian-Turkish dictionary: From the Marsigli Collection in Bologna - Siemieniec-Gołaś, Ewa (2015)
In the collection of oriental manuscripts preserved in the Marsigli Collection of the Biblioteca Universitaria di Bologna in Italy, one may find an anonymous and dateless dictionary prepared in the Italian language with a translation into Turkish. Judging by the watermark of the paper and certain features of the Turkish language, this manuscript is probably one of the earliest Italian-Turkish dictionaries. Moreover, the character of this work is quite unconventional since both Italian words and the transcribed forms of the Turkish vocabulary are written from right to left. The aim of the present book is to render accessible the Turkish vocabulary included in the dictionary and to present it together with the description of the manuscript.